A DISCOURSE ANALYSIS ON NARRATIONS OF AMERICAN CARTOON TRAILERS - PHẠM, THỊ THANH NGA (2016)
This study is carried out with the aim of examining the discourse features of narrations of American cartoon trailers (NACTs). The data for analysis in this thesis are 83 written forms of narrations from official trailers of American cartoons. These trailers come from the official websites of six major American cartoon film companies. In order to reach the goal, the researcher has employed a combination of a variety of methods such as descriptive, analytic and inductive ones. The thesis focuses on figuring out discourse features of NACTs in terms of their layout features, syntactic features, lexical choices, and cohesive devices. The findings of this study reveal that the layout of NACTs follows six patterns and has five main parts: Abstract, Orientation, Complicating Action, Evaluation and Coda. However, not all the parts are always presented in the narrations. With regard to syntactic features, simple sentences, passive sentences, parallel constructions, relative clauses, and imperative sentences are the most striking structures in NACTs. Besides, descriptive adjectives, time expressions, proper names, and pronouns denoting first and second persons are dominant lexical choices in NACTs. Finally, in terms of cohesive devices, grammatical cohesion and lexical one are investigated. The former includes reference and conjunction. The latter consists of repetition, synonymy, and super-ordinates. The findings reveal that reference, conjunction and repetition are devices that occur most frequently in NACTs. It is hoped that the results of the study will provide some practical applications for teaching and learning English for Vietnamese learners. This study may also be helpful to those who are working as copywriters and those who intend to participate in the task of writing film trailers.